Multitract percutaneous nephrolithotomy in staghorn calculus - Arvind P. Ganpule; M. Naveen Kumar Reddy; S.B. Sudharsan; Shaishav B. Shah; Ravindra B. Sabnis; Mahesh R. Desai (Asian Journal of Urology)
Staghorn calculi are branched stones which occupy a majority portion of the pelvicaliceal system. An untreated staghorn calculus over time can damage the kidney and deteriorate its function and/or cause life threatening sepsis. Total stone clearance is an important goal in order to eradicate any infective focus, relieve obstruction, prevent recurrence and preserve the kidney function. Percutaneous nephrolithotomy (PCNL) is currently the accepted first-line treatment option for staghorn calculi. The options available are single-tract PCNL with an auxiliary procedure like shockwave lithotripsy, single-tract PCNL with flexible nephroscopy, or multitract PCNL. Each has its own pros and cons. But the ultimate goal of treatment for any patient with staghorn calculi should be safety, cost-effectiveness, and to achieve total stone clearance. With this article, we review the management of staghorn calculi with multiple percutaneous (“multitract”) access, its advantages and disadvantages and its current position by studying the various published materials across the globe. Keywords: Percutaneous nephrolithotomy, Staghorn, Multitract, Kidney, Stone